2018
DOI: 10.1016/j.cmi.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vancomycin MIC creep in methicillin-resistant Staphylococcus aureus infections—a systematic review and meta-analysis

Abstract: We have found no evidence of the MIC creep phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 90 publications
1
52
1
1
Order By: Relevance
“…A global analysis (including 56 countries) based on the Tigecycline Evaluation and Surveillance Trial also demonstrated that the percentage of MRSA isolates with MICs of at least 2mg/L increased from 5.6% in 2004 to 11.1% in 2009 ( P < 0.001) . However, a systematic review and meta‐analysis failed to find evidence of the MIC creep phenomenon . Such differences may be explained by the fact that the MIC creep phenomenon may be influenced by differences in the susceptibility testing methods used (including storage of isolates) and differences in epidemiological and clinical factors among study sites .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A global analysis (including 56 countries) based on the Tigecycline Evaluation and Surveillance Trial also demonstrated that the percentage of MRSA isolates with MICs of at least 2mg/L increased from 5.6% in 2004 to 11.1% in 2009 ( P < 0.001) . However, a systematic review and meta‐analysis failed to find evidence of the MIC creep phenomenon . Such differences may be explained by the fact that the MIC creep phenomenon may be influenced by differences in the susceptibility testing methods used (including storage of isolates) and differences in epidemiological and clinical factors among study sites .…”
Section: Discussionmentioning
confidence: 99%
“…Olearo et al 28 31 However, a systematic review and meta-analysis failed to find evidence of the MIC creep phenomenon. 32 Such differences may be explained by the fact that the MIC creep phenomenon may be influenced by differences in the susceptibility testing methods used (including storage of isolates) and differences in epidemiological and clinical factors among study sites. 33,34 Therefore, dynamic monitoring of vancomycin MICs in a specific area is highly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 , 3 ] It is commonly used for methicillin-resistant Staphylococcus aureus (MRSA), ampicillin-resistant enterococci and Gram-positive organisms in patients allergic to penicillin. [ 4 6 ] Vancomycin is usually given by intravenous drip. In the treatment of Clostridium difficile-associated disease, vancomycin is taken orally.…”
Section: Introductionmentioning
confidence: 99%
“…3 Vancomycin is currently the drug to be chosen for treating many MRSA infections. 4 However, increasing minimum inhibitory concentration (MIC) of Vancomycin, though falls in the range of susceptibility, is reported worldwide. 5 Hence, the present study was carried to evaluate the vancomycin MIC values of strains of MRSA obtained from clinical samples.…”
Section: Introductionmentioning
confidence: 99%